Effect of globalization on inequality. A global study for 104 countries using quantile regressions - Cuesta Luzuriaga , Gisselle Lizeth (2021)
Inequality is one of the most worrying problems in society as it is evident in various areas of daily life. This is corroborated by several international organizations; Thus, the United Nations Development Program (UNDP, 2019), highlighted that, worldwide, 26 people had the same amount of money as the 3.8 billion poorest people in the world, causing greater malnutrition and disease. Where, the richest fifth of the population has higher educational levels than the poorest quintile Likewise, according to the World Income Inequality Database (WIID, ​​2020) showed that, at the regional level, the Middle East and Latin America are the regions more unequal, where its top decile captures 56% and 54% of the average national income, while Europe, with a concentration of 35% of income in the richest 10% of the population, is the most egalitarian. When people do not present the same socioeconomic conditions, they have different productivity, which, added to political problems, impede the development of countries (Argadoña, 2016; Perugini & Vladisavljević, 2020).